De novo Minimal Change Disease in an Adolescent after Pfizer-BioNTech COVID-19 Vaccination: A Case Report - Eva Pella; Pantelis A. Sarafidis; Maria-Eleni Alexandrou; Maria Stangou; Christina Nikolaidou; Dimitrios Kosmidis; Aikaterini Papagianni (Case Reports in Nephrology and Dialysis, 2022)
This is the first report in an adolescent of minimal change disease (MCD) after the first injection of the BNT162b2 COVID-19 vaccine (Pfizer-BioNTech) with complete remission following steroid treatment. An 18-year-old white male with no prior medical history complained of gastrointestinal symptoms 11 days after his vaccination. Ascites and lower extremity edema were observed a few days later. He was admitted to a hospital as laboratory testing revealed proteinuria of 10.5 g/24 h, normal creatinine levels, and serum albumin of 1.8 g/dL, confirming the presence of nephrotic syndrome. Immunology and serology tests were unremarkable. A diagnostic kidney biopsy showed no significant glomerular or tubular abnormalities in light microscopy with negative immunofluorescence. Treatment with methylprednisolone 48 mg daily was initiated. A week after discharge, proteinuria declined to 1.2 g/24 h, and edema had disappeared, and 6 weeks later, complete remission was evident. As COVID-19 vaccination has been associated with the development of de novo and relapsing MCD, and this case provides additional support for this possible correlation.